Phenotypic models of perfect adaptation by CD8+ T cells - Gaglione, SA (2019)
T cells receive continuous antigenic stimulation in peripheral tolerance, cancer, and chronic infection. Persistent antigen exposure induces an initial cellular response. However, over time, T cells become unresponsive to the stimulus and cease activity, a behaviour known as adaptation. Although it is generally known that T cells adapt to persistent stimuli, the properties of this adaptation remain understudied. This thesis aims to characterize phenotypes of T cell adaptation and to suggest the possibility of relating these phenotypes to basic network models that produce adaptation.